Epidemiological Survey on Traffic Accident Mortality Referred to the Forensic Medical Center of Chaharmahal and Bakhtiari Province During 2005-2016 - Mahmoud Mobasheri; Solieman Kheiri; Seifollah Bakhshi; Yadollah Ramezani; Mansour Firouzbakht (Shahrekord University of Medical Sciences, 2020)
Background and aims: The World Health Organization has listed Iran as the country with the highest number of driving accidents worldwide. Chaharmahal and Bakhtiari is among the top ten provinces in Iran. The aim of this study was to carry out an epidemiological survey on driving accidents resulting in deaths that were referred to the Forensic Medical Center. Methods: In this cross-sectional study, the data were obtained from the Forensic Medical Center in Shahrekord, the provincial capital, during 2005-2016. Data were analyzed using descriptive statistics and the chi-square test by SPSS. Results: The number of registered accidents causing death was 3001. The highest number of accidents (13.5%) occurred from August 23rd to September 22nd, which equates to the last months of the summer according to the solar calendar. Location wise, the highest number of accidents happened in Shahrekord (58.2%). In addition, men and married people were more involved in accidents compared to women and singles. The age group of 21-25 had the most number of accidents. Further, the main road had the highest percentage of accidents (86.7%) compared to freeways, by-ways, and rural roads. Finally, head trauma 1634 (60.7%) was the most important cause of death in people who were in car accidents. Conclusion: Based on these results, policymakers and planners have to carry out necessary positive interferences and plans in order to reduce the number of factors which increase car accidents. Eventually, accidents are usually caused by multiple elements and this makes it necessary to review and optimize the operational output of responsible organizations and offices and the cooperation between them.